Barefaced Cheating in China’s Bull Market for Fraud - Marcus, Jon (International Higher Education, 2013)
The scope and nature of fraud and other dishonesty in China's higher education admissions system, particularly as it applies to international study, is substantial and growing. Increased competition for places in Western universities has stimulated this phenomenon.